Thyroid hormone profile in apparently healthy pregnant women attending in a tertiary care hospital of Bangladesh - Khan, Murshed Ahamed; Hasanat, M.A.; Alam, Md. Jahangir; Hossain, Md. Anwar; Saleh, Ahmed Abu; Fariduddin, Md. (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Background: Thyroid dysfunction is not uncommon in pregnancy. It should be evaluated for better outcome of pregnancy. Objective: To observe the thyroid hormone profile in apparently euthyroid pregnant women of any trimester. Methods: This cross-sectional study investigated 350 pregnant women irrespective of gestational age [(age 24±4, m±SDyr; 1st trimester = 101, 2nd trimester=111, 3rd trimester=138) for thyroid stimulating hormone (TSH) and for free thyroxine (FT4)] to assess their thyroid function during pregnancy following the criteria of American Thyroid Association (ATA). Results: Most of the mothers were housewifes (93.1 %, 326/350) of whom 46.6% were primigravida. About 63% mother had associated goiter, 58% (204/350) were euthyroid and 41 % (142/350) were subclinical hypothyroid (SCH). Frequency of goiter (63% vs. 62%, euthyroid vs. dysfunction) was not significantly different between dysfunction and normal groups. FT4 significantly correlated with gestational age (r= - 0.131, p=0.014) and TSH level (r= - 0.612, p< 0.001). Conclusion: It is concluded that many of the apparently euthyroid pregnant mother have dysfunction as defined by ATA reference ranges for TSH and FT4. Simple screening for thyroid function may have greater implication for better pregnancy outcome.